(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Participants must actively participate in role-playing because of its interactive nature. Learners navigate these simulated interactions and acquire grammar principles by application rather than just memorization. Role-playing’s instantaneous feedback loop allows for prompt error correction and reinforcement, resulting in an ongoing cycle of learning that fixes mistakes as they arise.